Adolescence and puberty - Bancroft, John; Reinisch, June Machover (Kinsey Institute series, 1990)
Scientists from 10 disciplines contribute essays which explore various aspects of this critical stage in human development, in a volume designed for the benefit of social and developmental psychologists, psychologists interested in sexuality studies, and child and adolescent psychiatrists.